Recent Development of Extremophilic Bacteria and Their Application in Biorefinery - Daochen Zhu; Daochen Zhu; Wasiu Adewale Adebisi; Fiaz Ahmad; Sivasamy Sethupathy; Blessing Danso; Jianzhong Sun (Frontiers in Bioengineering and Biotechnology, 2020)
The biorefining technology for biofuels and chemicals from lignocellulosic biomass has made great progress in the world. However, mobilization of laboratory research toward industrial setup needs to meet a series of criteria, including the selection of appropriate pretreatment technology, breakthrough in enzyme screening, pathway optimization, and production technology, etc. Extremophiles play an important role in biorefinery by providing novel metabolic pathways and catalytically stable/robust enzymes that are able to act as biocatalysts under harsh industrial conditions on their own. This review summarizes the potential application of thermophilic, psychrophilic alkaliphilic, acidophilic, and halophilic bacteria and extremozymes in the pretreatment, saccharification, fermentation, and lignin valorization process. Besides, the latest studies on the engineering bacteria of extremophiles using metabolic engineering and synthetic biology technologies for high-efficiency biofuel production are also introduced. Furthermore, this review explores the comprehensive application potential of extremophiles and extremozymes in biorefinery, which is partly due to their specificity and efficiency, and points out the necessity of accelerating the commercialization of extremozymes.